“Complement fractionation” in natural diploid orchid species - Teoh, S.B. (Springer Verlag, 1982)
Four out of 10 diploid orchid species showed “complement fractionation” a complex cytological phenomenon, hitherto reported only in polyploid plants. The manifestation of this phenomenon during meiosis is the formation of chromosome subgroups resulting eventually in cells with more than the usual four sporads; five or six being the optimum number in the investigated orchid species. No implications whatsoever can be deduced as to the genetic or genomic constitution of the end products. The presence of the phenomenon in these orchid species could perhaps indicate a polyploid ancestry or concealed hybridity. The operation of “complement fractionation”, however, could be interpreted as an alternative evolutionary pathway opposed to polyploidy.